Strategies of Conflict Management During The Covid-19 Pandemic Health Student - M. Nurul Huda (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
This study used a quantitative method with a Descriptive Frequency Distribution Analysis design to find out the conflict management strategies used by students of STIKes Arrahma Mandiri Indonesia Pasuruan Hospital Administration. The instrument used in the study used a questionnaire, namely the Rahim Organization Conflict Inventory (ROCI) to measure the level of knowledge of Hospital Administration students about existing conflict management strategies. From the results of the analysis of this study, it is stated that the conflict mechanism strategy that is dominantly used by nursing students and nurses working in health institutions is more likely to use a collaboration strategy.